The results of many years of complex use of cycle- and power-ergometry in determining the physical capacity of young athletes - Khoroshukha, M. F.; Bosenko, A. I.; Mykhaliuk, Ye. L.; Filippov, M. M.; Хорошуха, М. Ф.; Босенко, А. І.; Михалюк, Євген Леонідович; Філіппов, М. М. (Запорізький державний медико-фармацевтичний університет, 2024)
Aim of the work: to assess the results of a complex use of cycle- and power-ergometry in determining the aerobic and anaerobic-aerobic performance in young athletes for the selection of criteria in predicting athletes’ sports abilities and performance results at competitions in certain sports. Materials and methods. Young athletes aged 15–16 (n = 636) took part in the study in which they represented two groups of athletes according to a training process direction: group A (n = 260) – speed-power sports (boxing, freestyle wrestling); group B (n = 376) – endurance sports (athletics, skiing, cycling, swimming). According to the results of their performance at competitions, all athletes were additionally divided into two groups: 1) a group of people who won prize places at competitions in their chosen sports – winners, 2) a group of their peers who unsuccessfully performed at competitions – outsiders. Physical working capacity was determined using two methods: cycle ergometric test PWC170 and power-ergometric test PWC170. Submaximal ergometric test PWC170 (Physical Working Capacity, PWC) is a method based on the determination of physical working capacity (load capacity) upon reaching a heart rate of 170 beats·min-1. Мета роботи – оцінити результати комплексного використання вело- і power-ергометрії у визначенні аеробної та анаеробно-аеробної працездатності юних спортсменів для вибору критеріїв під час прогнозування спортивних здібностей і виступу на змаганнях з окремих видів спорту. Матеріали і методи. У дослідженні взяли участь юні спортсмени віком 15–16 років (n = 636), яких за спрямованістю тренувального процесу поділили на дві групи: група А (n = 260) – швидкісно-силові види спорту (бокс, вільна боротьба); група Б (n = 376) – види спорту на витривалість (легка атлетика, лижний спорт, велоспорт, плавання). За результатами виступу на змаганнях усіх спортсменів додатково поділили на дві групи: 1 – група осіб, які отримали на змаганнях з обраних видів спорту призові місця (призери); 2 – група однолітків, які невдало виступили на змаганнях (аутсайдери). Фізичну працездатність визначали за допомогою двох методів: велоергометричного тесту PWC170 та power-ергометричного тесту PWC170. Субмаксимальний ергометричний тест PWC170 (від англ. Physical Working Capacity (PWC) – фізична працездатність) – метод, що ґрунтується на визначенні фізичної працездатності (потужності навантаження) при досягненні частоти серцевих скорочень 170 уд/хв-1.
Результати багаторічного комплексного використання вело- і power-ергометрії у визначенні фізичної працездатності юних спортсменів
Keywords: physical endurance; cycle-ergometry; powerergometry; results; young; athletes; фізична працездатність; велоергометрія; power- ергометрія; результати; юні спортсмени